Relationships Between Polyhedral Convex Sets and Generalized Polyhedral Convex Sets - Luan, Nguyen Ngoc; Nam, Nguyen Mau; Thieu, Nguyen Nang; Yen, Nguyen Dong (Journal of optimization theory and applications, 2023)
In this paper, we study some relationships between polyhedral convex sets and generalized polyhedral convex sets. In particular, we clarify by a counterexample that the necessary and sufficient conditions for the separation of a convex set and a polyhedral convex set obtained by Ng et al. (Nonlinear Anal. 55:845–858, 2003; Theorem 3.1) are no longer valid when considering generalized polyhedral convex sets instead of polyhedral convex sets. We also introduce and study the notions of generalized polyhedral multifunctions and optimal value functions generated by generalized polyhedral convex multifunctions along with their generalized differentiation calculus rules.